Strategy sustainable advantage and performance - West, G. Page (South-Western, 2010)
Provides a survey of modern management practice that integrates classic and contemporary principles. This text focuses on dynamic small to mid-sized 'local' businesses and entrepreneurial issues, giving students real-world insights and practical skills they can apply when beginning or continuing their careers.